PENGARUH HARGA, CELEBRITY ENDORSER, DAN SOCIAL MEDIA MARKETING TERHADAP INTENTION TO BUY PRODUK THE BODY SHOP - Soraya, Az’zahra Dinda; Suryadi, Nanang (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Beauty products in the modern era have experienced rapid development, one of which is skin care and cosmetic products. The development of skincare and cosmetic products is currently surging drastically with the arrival of products from within the country and abroad. The number of product choices can affect consumer intentions to buy according to the needs needed. This study was conducted to determine the effect of price, celebrity endorser, and social media marketing on product purchase intentions. This type of research is explanatory research which explains the causal relationship between research variables through hypothesis testing. The sampling technique used is non-probability sampling and purposive sampling method. The sample size used is 160 respondents with the provision that they are domiciled in Malang City and aged 20 to 39 years. Data analysis using SPSS 16.0. Based on the results of testing the three hypotheses, it can be concluded that the price variable has a positive and significant effect on product purchase intentions, the celebrity endorser variable has a non-positive and insignificant effect. on product purchase intentions, and social media marketing variables have a positive and significant effect on product purchase intentions.